AB0462 The Lack of Antidrug Antibodies Among Patients Treated with Tocilizumab: A Clue to Good Efficacy Profiles When Used as Monotherapy?. (9th June 2015) - Sigaux, J.; Hamze, M.; Daien, C.; Morel, J.; Krzysiek, R.; Pallardy, M.; Maillere, B.; Mariette, X.; Miceli-Richard, C.
Abstract : Background: Several lines of evidence demonstrate that anti-drugs antibodies (ADAbs) against anti-TNF are associated with low drug trough level, a mechanism underlying therapeutic failure and loss of response over time in rheumatoid arthritis (RA). Immunogenicity of Tocilizumab (TCZ) has been poorly studied to date and mainly relies on data provided by the company in their drug development program. Objectives: The aim of the study was to assess immunogenicity to TCZ and TCZ serum trough levels in real life patients with RA treated with TCZ. We also assessed whether preexisting CD4 T-cell repertoire specific to TCZ could be identified among healthy individuals in order to evaluate whether humans could mount a TCZ-specific T cells. Methods: 21 RA patients were prospectively assessed during the first 6 months after TCZ initiation; 19 other patients were consecutively included latter on, during treatment follow-up. Patients' clinical characteristics, serum trough TCZ levels and anti-TCZ ADAbs status were analyzed. TCZ serum trough levels and ADAbs were measured at different time points using a commercially available ELISA test (LISA Tracker - Theradiag). Anti-TCZ CD4 precursors were studied in 9 healthy controls. Healthy donors' monocyte-derived dendritic cells were generated from their PBMCs, loaded with TCZ or KLH as control and cultured with sorted CD4 T cells from the same donor. IFN-g ELISPOT was then used to detect TCZ-specific CD4 T cells. Results: 90 samples were analyzed for anti-TCZ ADAbs and TCZ trough levels. Only 3 patients had transient ADAbs (low titers and not observed 3 months later). TCZ serum trough level was lower among patients with high disease activity (DAS28>5.1) vs the others: 3.5±3, 7 μg/mL vs 10.2±10.2 μg/mL, p=0.006). There was no difference in TCZ serum trough level between patients in remission, low disease activity and moderate disease activity. None of the other patients' parameters were significantly associated or correlated with TCZ serum trough levels (gender, BMI, CRP). Only patients who had the infusion after the 5th week had a significant lower dosage of TCZ (p=0.0034). We analyzed 19 RA patients treated with TCZ associated with MTX and 16 RA patients with TCZ alone and found no significant difference between both groups (p=0.77). ELISPOT assays shown that in vitro CD4 T-cell response against TCZ was observed among 3 out of 9 healthy donors (Figure 1A-B ), i.e. to a similar range than the previously reported CD4 T-cell response against infliximab (IFX) 1 Conclusions: Our study demonstrates that the occurrence of ADAbs against TCZ is a very rare event. The reason of this low immunogenicity rate remains unknown. ELISPOT assays results suggest that anti-TCZ CD4 precursors exist among healthy donors at the same frequency as anti-IFX CD4. Thus, the low prevalence of ADAbs against TCZ could be the consequence of IL-6 blockade by TCZ, by acting on Tfh and/or B-cells at their different steps of differentiation and maturation. References: Delluc S et al. Quantitative analysis of the CD4 T-cell repertoire specific to therapeutic antibodies in healthy donors FASEB J. 2011 Jun;25(6):2040-8 Disclosure of Interest: None declared